2012
DOI: 10.1121/1.4757697
|View full text |Cite
|
Sign up to set email alerts
|

Pitch strength of noise-vocoded harmonic tone complexes in normal-hearing listeners

Abstract: To study the role of harmonic structure in pitch perception, normal-hearing listeners were tested using noise-vocoded harmonic tone complexes. When tested in a magnitude judgment procedure using vocoded versions generated with 2-128 channels, judgments of pitch strength increased systematically as the number of channels increased and reflected acoustic cues based on harmonic peak-to-valley ratio, but not cues based on periodicity strength. When tested in a fundamental frequency discrimination task, listeners c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…It has been suggested that these apparent species differences in perception could relate to the pitch cues that are available following cochlear filtering ( Cedolin and Delgutte, 2010 ; Shofner and Chaney, 2013 ). In particular, the growing evidence that cochlear bandwidths are broader in many non-human species ( Joris et al, 2011 ; Shera et al, 2002 ), including ferrets ( Alves-Pinto et al, 2016 ; Sumner et al, 2018 ), supports the possibility that they might process pitch cues in different ways from humans, as has been noted previously ( Shofner and Campbell, 2012 ; Shofner and Chaney, 2013 ).…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…It has been suggested that these apparent species differences in perception could relate to the pitch cues that are available following cochlear filtering ( Cedolin and Delgutte, 2010 ; Shofner and Chaney, 2013 ). In particular, the growing evidence that cochlear bandwidths are broader in many non-human species ( Joris et al, 2011 ; Shera et al, 2002 ), including ferrets ( Alves-Pinto et al, 2016 ; Sumner et al, 2018 ), supports the possibility that they might process pitch cues in different ways from humans, as has been noted previously ( Shofner and Campbell, 2012 ; Shofner and Chaney, 2013 ).…”
Section: Introductionsupporting
confidence: 60%
“…Although psychophysical experiments have demonstrated that humans can extract F0 using either resolved harmonics or unresolved harmonics alone ( Bernstein and Oxenham, 2003 ; Houtsma and Smurzynski, 1990 ; Shackleton and Carlyon, 1994 ), human pitch perception is generally dominated by resolved harmonics ( Ritsma, 1967 ; Shackleton and Carlyon, 1994 ; Shofner and Campbell, 2012 ). Marmosets can also use resolved harmonics to detect F0 changes ( Bendor et al, 2012 ; Song et al, 2016 ), whereas rodents (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, while we argue that marmosets are sensitive to spectral cues in these experiments, it is important to note that we cannot separate a spectral processing scheme in our experiments from a complimentary scheme utilizing temporal fine structure information (see, for example, Oxenham et al, 2004; Shofner and Campbell, 2012). For instance, similar predictions have been obtained whether one uses a harmonic template-based mechanism or one based on the waveform autocorrelation function (Cariani and Delgutte, 1996a,b; Meddis and O'Mard, 1997).…”
Section: Discussionmentioning
confidence: 79%
“…The large number of ERB bands used in the manipulation preserved much of the temporal structure of the original version, including some basic perception of pitch and phrasing (Shofner & Campbell, 2012). However, the replacement of all harmonic structure within bands by noise largely degraded the possibility of identifying instrumental timbres: in practice, all morphology-only variants sounded like a unique noisy instrument playing phrases of the same temporal morphology as the original (Figure 2(c)).…”
Section: Appendix A: Signal Manipulationsmentioning
confidence: 97%